Pengaruh Macromedia Flash dalam Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) terhadap Hasil Belajar Siswa Kelas X SMAN 12 Makassar (Studi pada Materi Pokok Ikatan Kimia) - Yanti Madong; Taty Sulastri; Sumiati Side (Jurusan Kimia FMIPA UNM, 2020)
The research is quasi experiment that aim to know the influence of using Macromedia Flash on cooperatif learning model type NHT to achievment of students of class X SMA Negeri 12 Makassar. The independent variable are NHT type cooperatif learning model with Macromedia Flash and without Macromedia Flash based in cooperatif learning model, and dependent variable is students’ achievment in chemical bonding main subject of learning. The populasi is whole student of X Grade SMAN 12 Makassar which consists of 8 classes. The sample include two classes such as X2 as an experiment class with 36 students and X3 class as a control class with 36 students The sampling technique is random with assumption that the population is homogeny. Data collection technique is obtained from objective test which consists of 20 items of multiple choice. The data analysis technique used are descriptive statistical analysis and inferential statistical analysis. The hypothesis test using t test shows that tcalculate > ttable = 2,97 > 1,67 on α ═ 0,05. Conclude that using Macromedia Flash on Cooperatif Learning Model Type NHT gives effected positive to toward student’s achievement of class X SMAN 12 Makassar on Chemical Bonding subject matter.